The Application of Chain Drill Techniques in Arabic Language Learning to Improve Students' Speaking Skills - Aditya Fitrah; Eva Lathifah Fauzia; Ade Arip Ardiansyah (PPPBA, 2025)
This research explores the impact of the chain drill method on enhancing Arabic speaking skills in seventh-grade students at MTsN 2 Kota Bandung throughout the 2024–2025 academic year. Even with the increasing focus on communicative competence in Arabic teaching, numerous students still find it challenging to create coherent, meaningful spoken sentences. This study seeks to fill this gap by investigating if structured repetition via chain drill activities can meaningfully improve students' speaking skills. A quasi-experimental design was utilized, consisting of an experimental group and a control group, with both groups containing 27 students. Classroom observations and speaking tests were utilized to gather data, with assessments conducted as pre-test and post-test. An independent samples t-test was utilized to analyze the data and assess the significance of group differences. The results from the pre-test showed similar initial proficiency levels (M = 52.30 for the experimental group and M = 51.20 for the control group). Post-intervention, the experimental group demonstrated a significant enhancement (M = 80.50), surpassing the control group (M = 70.23), with the difference being statistically significant (p < 0.05). These results indicate that the chain drill method effectively improves students' Arabic speaking skills by encouraging repetitive practice, reinforcing sentence formation, and fostering active participation. This research adds to the educational advancement of teaching the Arabic language by offering empirical data on the effectiveness of drill-based methods in enhancing oral skills within classroom environments.